Morbidity, and Short- and Intermediate-term Mortality, in Adults ≥60 Years Hospitalized with Respiratory Syncytial Virus Infection vs. Seasonal Influenza Virus Infection. (4th October 2017) - Tseng, Hung Fu; Sy, Lina S; Ackerson, Bradley; Fischetti, Christine; Slezak, Jeff; Luo, Yi; Solano, Zendi; Chen, Songyue; Shinde, Vivek
Abstract: Background: There is increasing evidence that respiratory syncytial virus (RSV) infection can cause serious health problems among older adults, whether healthy and community-dwelling, or high-risk. In older adults, RSV infection can lead to complications that are similar to those resulting from seasonal influenza infection. The aim of this study was to compare the morbidity and mortality in older adults ≥60 years hospitalized with RSV disease vs. those hospitalized with seasonal influenza. Methods: This cohort study included members of Kaiser Permanente Southern California aged ≥ 60 years who tested positive for RSV or influenza A/B by multiplex RT-PCR in clinical diagnostic testing during January 1, 2011 to June 30, 2015 and were hospitalized. For multiple eligible hospitalizations, only the first RSV hospitalization for the RSV cohort or first influenza A/B hospitalization for the influenza cohort was included. Electronic medical records for each hospitalized individual were used to extract necessary information, including baseline characteristics, symptoms, comorbidities, and outcomes. Results: The study included 664 RSV (mean age 78.5 years, 39.5% male) and 1922 influenza A/B (mean age 77.5 years, 49.7% male) hospitalizations. There were 310 (46.7%) RSV patients and 501 (26.1%) influenza patients with a diagnosis of pneumonia. There were 119 RSV patients (17.9%) vs. 272 (14.2%) influenza patients that were admitted to the intensive care unit during hospitalization (mean stay 6.8 vs. 7.8 days). The short-term mortality rate during hospitalization and within 90 days of discharge was 5.6% ( n = 37) and 7.4% ( n = 49) in the RSV cohort vs. 4.4% ( n = 85) and 6.7% ( n = 129) in the influenza cohort. The intermediate-term mortality rate within 91–180 days of discharge was significantly different between the RSV and the influenza cohorts (4.4% vs. 2.5%). Conclusion: RSV infection can lead to complications and severe outcomes that are similar to those of seasonal influenza in older adults. Effective prevention and treatment strategies such as vaccination and antivirals against RSV could potentially reduce the burden of RSV infection as well as complications from disease. Disclosures: H. F. Tseng, Novavax: Grant Investigator, Research grant. L. S. Sy, Novavax: Collaborator, Research grant. C. Fischetti, Novavax: Collaborator, Research grant. J. Slezak, Novavax: Collaborator, Grant recipient. Y. Luo, Novavax: Collaborator, Grant recipient. Z. Solano, Novavax Inc.: Collaborator, My employer received research funds to conduct the study. S. Chen, Novavax: Collaborator, Research grant. V. Shinde, Novavax Inc.: Collaborator, My employer received research funds to conduct the study.